Hörby kommun i förändring : utveckling för framtiden - Nilsson, Amanda (SLU/Landscape Architecture (until 121231), 2010)
We live in an exciting society, characterized by continuous changes and challenges. The effects of the globalization are widespread. The continuous flow of people, capital and goods follows in the wake of advances in communications, transport and information technology, resulting in a changed situation for different stakeholders in the society. This situation leads to increased cooperation and exchange, but also increased competition. The primary means of collecting empirical data for this study was interviews and a document study. The objective is to describe how Hörby municipality is working with the municipal development and the underlying reasons. The purpose is to create an understanding of how the planning of a rural municipality may be affected by the changes and development on a larger scale, both regionally and globally. Thus, studying the municipality based on both a regional and a global perspective. My study is based on three different questions. The first is focused around the central ambitions and specific proposals that can be found at the local level for development of Hörby municipality and what lies behind them. Topic number two deals with similar issues in Region Skåne (Skåne Regional Council) and the third is a comparison between the regional and local level. The study has resulted in a number of results. The key ambitions of the local development of Hörby municipality are rooted largely in the vision of the municipality, a vision that reflects the municipality's desire to evolve. The municipality's main areas of development can be found in the northwestern part of the municipality, a part under heavy population pressure. The factors underlying the municipality's efforts include the development of the Øresund Region and the Øresund Bridge which is a central point. Entering the EU is another important aspect. These factors have led to changes in flows of people, goods and capital, namely the impact of globalization. Regional efforts are carried out based on the same background factors as the local level. A large part of the efforts is to identify the assets and opportunities of Skåne Region to become an attractive region for business establishment, residents, tourists, etc. As regards to the comparison between the local and regional level, it is concluded that the ideas of development in many ways are similar. What makes them different, however, are parts of the implementation where the infrastructure is an important aspect of the displayed vision. Since the region has to take into account a wider perspective, the priorities are somewhat different. The concluding results of this thesis is that the municipality has a vision that reflects an ideal image of what the municipality wants to achieve, an ideal image that is difficult to achieve. Some of these problems is to reconcile the issue of continuous growth with environmentally sound development.